Pemanfaatan Minyak Jelantah Untuk Pembuatan Lilin Aromatherapy dan Sabun di Desa Basungkai - Syahrozi, Syahrozi; Rahayu, Elis Sri; Rosalia, Alderina (Fakultas Teknik Universitas Palangka Raya, 2025)
Cooking oil is a food processing ingredient that is commonly used by Indonesian people. Various types of food require frying in the processing process. Indonesian people are accustomed to using cooking oil more than twice, which is usually called used cooking oil. The aim is to reduce household expenses. Many people do not know the physical quality of cooking oil that is used more than twice. Use of used cooking oil can increase the risk of cancer, bacterial infections, degenerative diseases (Alzheimer's and Parkinson's) and obesity. The method implemented in carrying out community empowerment has several stages: (1) Providing education on healthy living, (2) demonstration and practice, utilization of used cooking water and (3) assistance in carrying out activities whose targets are the perpetrators of family sustainability activities, namely PKK Association (Pemberdayaan Kesejahteraan Keluarga/ Family Welfare Empowerment). This Community Empowerment activity provides knowledge in the health sector, and the use of used cooking oil to make clothes washing soap, hand washing soap and aromatherapy candles which are beneficial for everyday life.